Application Of The Buzz Group Method In Cognitive/Mathematics Learning To Increase Learning Activities In Recognizing Number Symbols For Students Age 4 - 5 Years At Aisyiyah Bustanul Athfal Waikabubak Kindergarten - SRI WATI; Zulhayati Zulhayati (Early Childhood Education Development and Studies (ECEDS), 2022)
This study aims to determine whether the application of the Buzz Group method to cognitive/mathematics learning can improve student learning outcomes related to counting the number of numbers. This research includes classroom action research (CAR) conducted at Aisyiyah Bustanul Athfal Kindergarten, Waikabubak City, West Sumba Regency. The research was conducted in the even semester of the 2022/2023 academic year. The research subjects were group A students and a teacher. Data collection instruments in this study include observation sheets, LKPD, and documentation. The results showed that the application of the Buzz Group method could improve the learning outcomes of Aisyiyah Bustanul Athfal Waikabubak Kindergarten students regarding the concept of numbers by using objects 1 to 10. This was illustrated by the increase and achievement of criteria for teacher activity, student activity, and student learning outcomes after studying with the Buzz Group method. The percentage of students who achieve learning outcomes in cycle 2 is 75%. This result increased compared to the learning outcomes of cycle 1 where the percentage of students who achieved learning outcomes was only 25%. The approach used in this study is a qualitative approach and a quantitative approach. This study consisted of quantitative data, namely data obtained from student learning research, while qualitative data was obtained from observations of activities inside and outside the classroom.